Embellish me : how to print, dye, and decorate your fabric - Wisbrun, Laurie (Interweave, 2012)
A guide to achieving the perfect surface finish for fabric-based projects, this book includes comprehensive step-by-step instructions for tie-dyeing, bleaching, and shibori; block, silk-screen, and digital printing; and beading, embroidery, and appliqué.